(untitled) (Global Journal of Human-Social Science, 2019)
This paper makes a review of literature on growing wildlife trafficking, more specifically to South Asia. It intends to analyze the nature of this illegal trade and evaluate practices in institution building for the control of wildlife crimes. Based on review and consultation with the stakeholders, we conclude that socio-cultural fabrics in East Asian countries are fuelling the demand side of the trafficking from this region whereas the poverty in the vicinity of national park areas coupled with the connection to mediators and smugglers is causing the supply side chain. The high prices in the international market are mainly caused by the misconception mainly regarding the medicinal values of some wildlife products. The poaching model discussed in the paper concludes that the conservation effort/cost needs to move along with the stock of the wildlife and the poaching efforts, but the lack of effective monitoring mechanism for the census of wildlife is causing the gap between them and the continuation of the crime in the region.